STRENGTHENING ACADEMIC LITERACY THROUGH GUIDANCE IN WRITING ACCREDITED JOURNAL ARTICLES FOR UNPARI BIDIKMISI STUDENTS - Agung Nugroho; Inda Puspita Sari; Cekman (LP3MKIL, 2026)
Low academic literacy among students, particularly in writing scientific articles for publication in accredited journals, is a persistent problem among Bidikmisi students in the Indonesian Language and Literature Education Study Program at PGRI Silampari University (UNPARI). This condition results in low scientific publication skills and delays in the completion of final assignments. This community service activity aims to improve students' academic literacy through mentoring in writing scientific articles based on accredited journals. The method used is a collaborative, participatory approach with workshops, writing clinics, and ongoing mentoring. Evaluation was conducted through pre- and post-tests, observations, and analysis of student writing. The results of the activity showed a significant increase in academic literacy, from an average score of 61.4 to 87.2. Eighty-eight percent of students were able to draft scientific articles, and 70% reached the journal submission stage. Furthermore, there was an increase in student motivation and confidence in scientific writing. The conclusion of this activity is that mentoring in writing scientific articles based on strengthening academic literacy is effective in improving Bidikmisi students' publication skills, both in terms of knowledge, skills, and academic attitudes.